Modeling Jordanian audience engagement and news credibility in the digital media era: a PLS-SEM approach - Al-Mshashaqbeh, Yousef Awad Ahmad (Frontiers in Communication, 2025)
The rise of digital news has reshaped the landscape of news consumption, especially in emerging media environments such as Jordan, where audiences increasingly depend on online and social platforms for information. This study examines how Trust in Digital News (TND) and Social Media Use (SMU) influence Audience Engagement (AE) and Perceived News Credibility (PNC) among Jordanian users. A two-step methodological approach was adopted: first, a bibliometric mapping was conducted to identify research trends and gaps in digital media studies; second, Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied to survey data collected from 1,200 respondents. The results demonstrate that TND has a significant positive effect on AE (β = 0.45, p < 0.001) and PNC (β = 0.28, p < 0.01). SMU also shows a positive and significant impact on AE (β = 0.32, p < 0.01), but only a weakly significant effect on PNC (β = 0.15, p = 0.051). AE emerges as the strongest predictor of PNC (β = 0.56, p < 0.001), underscoring its mediating role in linking engagement and credibility. These findings highlight the crucial role of trust and interaction in strengthening perceptions of credible digital journalism, offering practical implications for media professionals and policymakers aiming to foster informed, democratic, and trust-based public discourse in the algorithmic information age.